Pemulihan Dampak Pencemaran Udara bagi Kesehatan Masyarakat Indonesia - Candrasari, Satya; Clarissa, Eleane Cyrilla; Kusumawardani, Fadilla; Pattymahu, Gracia Cristabel Henrietta; Eugenia, Janice Florence; Cahyadi, Larissa Belva; Silvian, Vergio; Syabanera, Nasya Dochka (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Pollution is a problem that never ends. These problems can also have a negative impact on health and the environment, such as causing respiratory problems, health problems, environmental damage and climate change. This problem is something that needs to be considered and researched in order to know the steps and what the efforts to deal with air pollution. In an effort to do this, this research was carried out using descriptive qualitative methods with literature study as the research method. Based on the observations, to reduce the impact of air pollution, several solutions have been proposed, Starting from exercising which contributes to respiratory health, planting trees which can help filter harmful particles from the air. Reducing motor vehicle use, and using environmentally friendly vehicles is also recommended. Using environmentally friendly products also can help reduce plastic waste. Beside that, Proper waste processing is also the key to reducing the negative impact of burning waste on air quality.